The Impact of Service Quality and Institutional Image on Students' Behavioral Intentions in Accredited Madrasah Aliyah (Islamic Senior Secondary School) in Malang, Indonesia - Imdad Rabbani; Wahidmurni; Indah Aminatuz Zuhriyah (Jurnal Pendidikan Islam, 2024)
Purpose – This study aims to examine the influence of service quality and institutional image on the behavioral intention of students at Madrasah Aliyah (Islamic Senior Secondary School) accredited A in Malang. Understanding these factors is crucial for educational institutions to maintain their reputation and competitive edge by influencing student perceptions positively, thereby fostering behaviors that benefit the institution, such as recommendations and continued enrollment. Design/methods/approach – This correlational research employs a quantitative approach with data collected through online surveys. The sample consists of 354 students from accredited Madrasah Aliyah in Malang, selected using proportionate random sampling. The study analyzes the relationships between service quality, institutional image, and students' behavioral intention using multiple linear regression. Findings – The results reveal a significant positive impact of both service quality (β = 0.089, p < 0.001) and institutional image (β = 0.146, p = 0.010) on students' behavioral intention. The combined influence of these variables accounts for 64.6% of the variance in behavioral intention, suggesting that improvements in these areas are likely to enhance student loyalty and advocacy. Research implications – These findings underscore the importance of managing service quality and institutional image to foster positive behavioral intentions among students, which in turn can lead to increased student retention and attraction. The study also suggests further research into other factors influencing student behavior and expanding the application of these findings to other educational settings